Penentuan Strategi Pengelolaan Sampah Rumah Tangga dengan Metode SWOT (Studi Kasus: Bangunjiwo Kasihan Bantul DIY) - Astuti, Reni Dwi; Maknun, Lu’luil (Rekayasa, 2025)
Waste is one of the problems in Bantul Regency, especially in Bangunjiwo Village, Kasihan District. Bangunjiwo Village has a waste generation of 8.39 tonnes per day, but only 0.03 tonnes can be managed, and the rest is disposed of in landfills. The contributing factors are low public awareness of waste management and suboptimal waste management. The purpose of this study is to propose a waste management strategy to reduce the volume of waste disposed to landfill. This research uses the SWOT method as a strategy planning tool by considering the internal factors of the waste management party and the external factors that surround it. Strategy determination is based on the calculation of the IFAS and EFAS matrix which serves to determine the quadrant position. Then the quadrant position is used as the basis for determining waste management strategies. The results showed that the position of waste management in Bangunjiwo Village is in quadrant 1 (S-O), which means that it must optimise internal strengths and existing opportunities. The strategy formed is a strategy of collaboration between BUMDes and private waste collectors by utilising funds provided by the Regency Government and utilising the existing large land area, as well as increasing the empowerment of Human Resources (HR) for waste management.